DEVELOPMENT OF SPECTROPHOTOMETRIC METHOD FOR ALLOPURINOL IN URINE BASED ON THE DIAZOTIZATION REACTION - Yazid, Edy Agustian (Publication Policy, 2014)
A simple, rapid, low cost, accurate and sensitive spectrophotometric method for the determination of allopurinol (ALP) in urine was developed. This method is based on the reaction of diazotized sulfanilamide with ALP as coupling agent in an alkaline medium. The resulting intense yellow dye has a maximum absorption at 400 nm and stable for more than 1 hour. The Beer’s law limits was obeyed over the concentration range of ALP in aqueous medium from 5.0-50 g/mL. The molar absorptivity and Sandell’s sensitivity were obtained 2.5 × 103 L mol–1 cm–1 and 0.061 μg cm–2 /0,001 absorbance unit, respectively. The optimum reaction conditions and other analytical parameters have also been investigated. The correlation coefficient (r) was obtained 0.999. LOD and LOQ were found 2.2 μg/mL and 7.5 μg/ mL, respectively. The percent recovery and relative standard deviation (RSD) were found 99.18-100.10 % and 0.3-1.3 %, respectively. The proposed method can be applied successfully to assay ALP in urine by standard addition method and can be considered as an alternative method for determination ALP in the urine samples.